PREVALENCE OF CHRONIC ENDOMETRITIS IN CASES OF RECURRENT IMPLANTATION FAILURE- A RETROSPECTIVE STUDY - Dr Alka Gahlot; Dr Divya Jethwani (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Chronic endometritis being chronic in nature is accidentally diagnosed during work up of infertility. Chronic endometritis is chronic inflammatory condition characterized by presence of plasma cells infiltrating endometrial stroma. It is being associated with cases of recurrent implantation after IVF - ICSI Hysteroscopy has high negative predictive value in diagnosing CE: CD – 138 immunohistochemistry presents on plasma cells is suggested for more accurate diagnosis of CEObjective: The objective of our study is to evaluate the prevalence of chronic endometritis in women with recurrent implantation failure after ICSI.Material & methods : Our study included 152 patients with recurrent implantation failure after 2 or more IVF – ICSI despite having good – quality embryos. Hysteroscopy followed by endometrial biopsy was performed. H & E staining and immunohistochemistry was done on biopsies sample. Association between hysteroscopic findings and immunohistochemistry and prevalence of chronic endometritis was evaluated.Results: Out of 152 included in this study; 34.2% were detected by hysteroscopy, 29.6% were detected by CD – 138 IHC and 21% were detected by both the modalities. The sensitivity, specificity, PPV and NPV of hysteroscopy in the study was 71.7%, 81.3%, 61.5% and 87% respectively. The diagnostic accuracy of hysteroscopy in diagnosing CE was 78.2%.Conclusion: The negative predictive value and specificity of hysteroscopy is high and combining two diagnostic methods (hysteroscopy and CD – 138 IHC) will detect most cases of chronic endometritis.